Identification and Characterization of MicroRNAs in the Goat (Capra hircus) Rumen during Embryonic Development - Zhong, Tao; Hu, Jiangtao; Xiao, Ping; Zhan, Siyuan; Wang, Linjie; Guo, Jiazhong; Li, Li; Zhang, Hongping; Niu, Lili (Frontiers in Genetics, 2017)
The rumen is an important digestive organ in ruminants. Numerous regulatory factors including microRNAs (miRNAs) are involved in embryonic organ development. In the present study, miRNAs expressed in the rumens of goats (Capra hircus) and their potential roles in the pathways involved in rumen development were identified using high-throughput sequencing. Histological morphology revealed a distinct difference in each layer of rumen during the period from embryonic day 60 (E60) to embryonic day 135 (E135). We determined the expression profiles of miRNAs in the goat rumen, and identified 423 known miRNAs and 559 potentially novel miRNAs in the E60 and E135 embryonic rumen, respectively. Bioinformatics analysis annotated the 42 differentially expressed miRNAs and the top ten most highly expressed miRNAs of the two libraries to 48 and 38 gene ontology (GO) categories, as well as to 168 and 71 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. The expression patterns of eight randomly selected miRNAs were validated by stem-loop quantitative reverse transcription PCR (qRT-PCR), suggesting that the sequencing data were reliable. We profiled the genome-wide expression of rumen-expressed miRNAs at different prenatal stages of rumen tissues, revealing that a subset of miRNAs might play important roles in the formation of the rumen layers. Taken together, these findings will aid the investigation of dominant rumen-related miRNA sets and help understand the genetic control of rumen development in goats.